PERAN PEMBELAJARAN GEOGRAFI TERHADAP PEMAHAMAN MITIGASI BENCANA - Noviansyah, Rony (Jurnal Pendidikan Geografi Gea, 2014)
Geography is a process of learning and interaction between teacher and pupil in reviewing interaction, interrelation and integration of symptoms - symptoms surface of the earth, learning is one of the priorities in disaster risk reduction actions. This study aims to determine the level of students' understanding of disaster mitigation in North Bandung area, which is one of the disaster-prone areas, be it earthquakes, volcanoes and ground movement. The approach in this study uses a quantitative approach to survey methods with a sample of 176 were conducted by proportional random sampling of 2769 students in the areas of disaster-prone areas of North London which consists of 10 schools both public and private schools. Based on the results of the study, students who do not understand the disaster and disaster mitigation in the North London area is still quite high with a percentage of 43.7%, while quite aware of the potential for disaster in the North London area of 31.8% and are aware of the potential for disaster in the Region North Bandung by 24.5%. There is still a lack of understanding of the students in North Bandung disaster mitigation factors that cause is the method used by the teacher in presenting material related to disaster mitigation and disaster only use the lecture method. Recommendations in the study include making a concept in which the charged device pembeajaran mitigation and expected learning device is charged mitigation tested on high school students by further research.Keywords: The Role of Learning, Understanding Disasters and Disaster Mitigation.